TEACHER LEADERSHIP IN THE LABORATORY IN DEVELOPING STUDENTS' DISCIPLINE AND CREATIVE CHARACTER - Natsir, Nasrah (Universitas Negeri Medan - Indonesia, 2024)
The aim of this research is to find out (1) how teacher leadership develops students' disciplined character through learning in the laboratory, (2) how teacher leadership develops students' creative character through learning in the laboratory. This research uses a qualitative descriptive approach, namely to understand the meaning behind visible learning activities, to understand the interaction of teachers and students, to understand the feelings of teachers and students, to develop theories, and to ensure the truth of the data. Data was collected using observation study methods, interviews, and subsequent documentation, the data is analyzed using structured steps, namely reducing the data, exposing/presenting the data, drawing conclusions. The results of this research are: (1) the form of teacher leadership in learning in the laboratory to develop students' disciplined character can be seen from the methods of habituation, example, telling stories, and discussions used by laboratory teachers; (2) the form of teacher leadership in learning in the laboratory to develop students' creative character can be seen from the methods of habituation, example, telling stories, discussions and simulations used by laboratory teachers.